A Hydrazone Ligand for Iridium-Catalyzed C-H Borylation Enhanced Reactivity and Selectivity for Fluorinated Arenes - Peruzzi, Christopher D (Organometallics, 2024)
© 2024 The Authors. Published by American Chemical Society.